Predictors of diet quality as measured by Malaysian healthy eating index among aboriginal women (Mah Meri) in Malaysia - Chong, Su Pei; Appannah, Geeta; Sulaiman, Norhasmah (MDPI, 2019)
Socioeconomic status and nutrition knowledge are the determining factors of food choices. However, their relationship with diet quality is ambiguous among aboriginal women in Malaysia. Henceforth, the objective of this study was to examine diet quality and its predictors among the aboriginal women from the Mah Meri ethnic group in Malaysia. Data on socioeconomic characteristics, nutrition knowledge, and 24-h dietary recalls were obtained through face-to-face interviews with the respondents. Household food insecurity was assessed using Radimer/Cornell Hunger and Food Insecurity Instrument. The Malaysian Healthy Eating Index (HEI) was used to measure the diet quality of this population. The overall diet quality of the respondents was poor, with a mean Malaysian HEI score of 45.3%. Household income (r = 0.242, p < 0.001) and nutrition knowledge (r = 0.150, p < 0.05) were positively correlated with diet quality. More importantly, the predictors of diet quality were marital status (β = 0.181, p < 0.01), household income (β = 0.237, p < 0.001), food security status (β = −0.151, p < 0.01), and fat intake (β = −0.438, p < 0.001). Women being married and those with higher household income was associated with a better diet quality among Malaysian aborigines.